Synthesis of Activated Carbon from Eichhronia Crassipes Plant as Adsorbent for the Removal of Phenol from Aqueous Solution - Ali, Hussain Mohammed; Zageer, Dheaa; Alwash, Atheel H (Al-Nahrain Journal of Science, 2019)
For a friendly environment, adsorbents are prepared from harmful natural sources to reduce their impact on the environment. The preparation of activated carbon from the Eichhornia crassipes was done by carbonization at 450C°, followed by activation step at 800C°. The adsorption processes were carried out by the batch system to determine the optimal conditions for the removal of phenol from the aqueous solutions. Different parameters were used in batch experiments such as initial concentrations of phenol (in the range from 10-100 ppm), pH (from 2-12), temperature (from 298-328k), AC dosage (from 0.09-0.4g). All the adsorption experiments were carried out in thermostat shaker at 150 rpm. The removal percentage of phenol on activated carbon was 98.2% at optimum conditions of 10 ppm initial phenol concentration, 25 minutes, pH=7, 308 k, 0.2 g of AC dosage). The thermodynamic functions of phenol adsorption were studied at different temperatures. The values of Gibbs free energy (∆G) at maximum removal with temperatures (298, 308, 318 and 328K) was (-5.17, -6.83, -8.22, -8.48) respectively and enthalpy ∆H, entropy ∆S values was 29.22 and 0.114. The activated carbon extracted from Eichhornia crassipes has a double benefit. first, to remove various organic pollutants such as phenols in aqueous solutions and the second, to create a clean water environment free of this plant found in Iraqi waters.